Proceedings of the 2nd International Conference on Law, Social Science, Economics, and Education, ICLSSEE 2022, 16 April 2022, 2022
DOI: 10.4108/eai.16-4-2022.2320070
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of MSMEs Growth on the Open Unemployment Rate in West Java Province

Abstract: One of Indonesia's national development plans is held in order to realize efforts to improve people's welfare. People's businesses that have the largest contribution as an important pillar in economic growth in Indonesia are Micro, Small and Medium Enterprises (MSMEs). This sector business has a role in supporting the economy and is able to survive in any situation, as evidenced by the 1998 monetary crisis. The purpose of this study is to analyze the effect of MSME growth on the decline in the open unemploymen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…This high percentage shows that unemployment is one of the problems in the development of this industrial revolution era. As an effort to reduce the unemployment rate, the implementation of Micro, Small and Medium Enterprises (MSME) to Large Enterprises is another alternative so that the working age population in Indonesia can do it (Gherghina et al, 2020;Supandi et al, 2022). In fact, the number of entrepreneurs in Indonesia is still lower than other countries in the Southeast Asia region.…”
Section: Introductionmentioning
confidence: 99%
“…This high percentage shows that unemployment is one of the problems in the development of this industrial revolution era. As an effort to reduce the unemployment rate, the implementation of Micro, Small and Medium Enterprises (MSME) to Large Enterprises is another alternative so that the working age population in Indonesia can do it (Gherghina et al, 2020;Supandi et al, 2022). In fact, the number of entrepreneurs in Indonesia is still lower than other countries in the Southeast Asia region.…”
Section: Introductionmentioning
confidence: 99%
“…Research by [14], [19], [24] found that SES has a significant positive effect on the growth of SMEs in West Java Province. The study found that entrepreneurs with higher levels of education and experience had higher levels of business performance and were more likely to adopt new technologies and business practices.…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…While West Java Province is known as the largest MSME producing province in Indonesia [19], and there are ongoing efforts to support their growth [14], there is no specific data on their current growth rate. Some studies have investigated the effect of MSME growth on unemployment rates in West Java [24], while others have highlighted the significant contribution of MSMEs to job creation in Indonesia [25]. A recent study conducted a survey of 15 provinces in Indonesia, with around 60% of surveyed MSMEs located in Java, including West Java Province [20].…”
Section: Introductionmentioning
confidence: 99%
“…Pemerintah kota telah membentuk gugus tugas khusus untuk pemulihan ekonomi di kota tersebut, yang telah ditugaskan dengan tugas-tugas komprehensif untuk mendukung kegiatan ekonomi di Bandung. UMKM di Bandung menghadapi tantangan dalam mempertahankan bisnis mereka, dan tingkat daya saingnya masih rendah (Nurani et al, 2020;Supandi et al, 2022). Penelitian (Noviaristanti & Huda, 2022;Nurani, 2021;Saputri & Utami, 2023;Supandi et al, 2022) juga menyoroti bahwa skema pembiayaan untuk UMKM masih terbatas, yang merupakan salah satu faktor yang menyebabkan UMKM di kota Bandung memiliki daya saing yang rendah.…”
Section: Pendahuluanunclassified
“…UMKM di Bandung menghadapi tantangan dalam mempertahankan bisnis mereka, dan tingkat daya saingnya masih rendah (Nurani et al, 2020;Supandi et al, 2022). Penelitian (Noviaristanti & Huda, 2022;Nurani, 2021;Saputri & Utami, 2023;Supandi et al, 2022) juga menyoroti bahwa skema pembiayaan untuk UMKM masih terbatas, yang merupakan salah satu faktor yang menyebabkan UMKM di kota Bandung memiliki daya saing yang rendah. Makalah tersebut menyarankan bahwa implementasi manajemen sumber daya manusia pada skala UMKM adalah solusi yang disarankan untuk meningkatkan tingkat pola pikir hijau di antara tenaga kerja di sektor industri kreatif UMKM.…”
Section: Pendahuluanunclassified